Colonization of rice roots with methanogenic archaea controls photosynthesis‐derived methane emission. (27th January 2015) - Pump, Judith; Pratscher, Jennifer; Conrad, Ralf
Summary The methane emitted from rice fields originates to a large part (up to 60%) from plant photosynthesis and is formed on the rice roots by methanogenic archaea. To investigate to which extent root colonization controls methane (CH4) emission, we pulse‐labeled rice microcosms with 13CO2 to determine the rates of 13CH4 emission exclusively derived from photosynthates. We also measured emission of total CH4 (12+13CH4), which was largely produced in the soil. The total abundances of archaea and methanogens on the roots and in the soil were analysed by quantitative polymerase chain reaction of the archaeal 16S rRNA gene and the mcrA gene coding for a subunit of the methyl coenzyme M reductase respectively. The composition of archaeal and methanogenic communities was determined with terminal restriction fragment length polymorphism (T‐RFLP). During the vegetative growth stages, emission rates of 13CH4 linearly increased with the abundance of methanogenic archaea on the roots and then decreased during the last plant growth stage. Rates of 13CH4 emission and the abundance of methanogenic archaea were lower when the rice was grown in quartz‐vermiculite with only 10% rice soil. Rates of total CH4 emission were not systematically related to the abundance of methanogenic archaea in soil plus roots. The composition of the archaeal communities was similar under all conditions; however, the analysis of mcrA genes indicated that the methanogens differed between the soil and root. Our results support the hypothesis that rates of photosynthesis‐driven CH4 emission are limited by the abundance of methanogens on the roots.